10.1111/acn.v9999.9999 (CrossRef Listing of Deleted DOIs, 2000)
AIMS: Periodontitis among nursing home residents is increasing as more older adults retain their dentition. Evidence on the impact of periodontal therapy on their oral microbiota is limited. We aimed to assess the effect of outreach-based supra- and sub-gingival instrumentation on the periodontal microbiome. MATERIALS AND METHODS: In this secondary analysis of an RCT, 36 residents (mean age 85 ± 6 years) with periodontitis had been randomised to supra- and sub-gingival instrumentation (mean duration 14.3 ± 5.2 min) or a 3-month control. Supragingival and subgingival plaque samples were collected at baseline and 3 months. Bacterial 16S rRNA sequencing and mixed-effects modelling were used to assess alpha/beta diversity, dysbiosis index and differential abundance between groups over time. RESULTS: The intervention group showed clinical improvements, with bleeding on probing decreasing from 45% ± 20% to 35% ± 16% and probing pocket depth decreasing from 4.5 ± 0.5 to 4.0 ± 0.5 mm. Dysbiosis was reduced compared with controls (β = -1.97, p = 0.0008). Beta-diversity confirmed microbial shifts (R2 = 0.0075, p = 0.025), characterised by decreases in differential abundance of Treponema and Fretibacterium and increases in Lactobacillus and Actinomyces. CONCLUSIONS: A pragmatic outreach-based supra- and sub-gingival instrumentation reduced microbial dysbiosis and improved periodontal parameters in institutionalised older adults, supporting its effectiveness in nursing home care. TRIAL REGISTRATION: German Clinical Trials Register (DRKS) registration number: DRKS00029392.